Isotopic, carbon and minor element composition of the Sancerre sediments (Jurassic, Paris Basin) - Michael Hermoso; Fabrice Minoletti; Pierre Pellenard (PANGAEA, 2017)
One of the most elusive aspects of the Toarcian oceanic anoxic event (T-OAE) is the paradox between carbon isotopes that indicate intense global primary productivity and organic carbon burial at a global scale, and the delayed expression of anoxia in Europe. During the earliest Toarcian, no black shales were deposited in the European epicontinental seaways, and most organic carbon enrichment of the sediments postdated the end of the overarching positive trend in the carbon isotopes that characterises the T-OAE. In the present study, we have attempted to establish a sequence stratigraphic framework for Early Toarcian deposits recovered from a core drilled in the Paris Basin using a combination of mineralogical (quartz and clay relative abundance) and geochemical (Si, Zr, Ti and Al) measurements. Combined with the evolution in redox sensitive elements (Fe, V and Mo), the data suggest that expression of anoxia was hampered in European epicontinental seas during most of the T-OAE (defined by the positive carbon isotope trend) due to insufficient water depth that prevented stratification of the water column. Only the first stratigraphic occurrence of black shales in Europe corresponds to the "global" event. This interval is characterised by >10% Total Organic Carbon (TOC) content that contains relatively low concentration of molybdenum compared to subsequent black shale horizons. Additionally, this first black shale occurrence is coeval with the record of the major negative Carbon Isotope Excursion (CIE), likely corresponding to a period of transient greenhouse intensification likely due to massive injection of carbon into the atmosphere?ocean system. As a response to enhanced weathering and riverine run-off, increased fresh water supply to the basin may have promoted the development of full anoxic conditions through haline stratification of the water column. In contrast, post T-OAE black shales during the serpentinum and bifrons Zones were restricted to epicontinental seas (higher Mo to TOC ratios) during a period of relative high sea level, and carbon isotopes returning to pre-T-OAE values. Comparing palaeoredox proxies with the inferred sequence stratigraphy for Sancerre suggests that episodes of short-term organic carbon enrichment were primarily driven by third-order sea level changes. These black shales exhibit remarkably well-expressed higher-frequency cyclicities in the oxygen availability in the water column whose nature has still to be determined through cyclostratigraphic analysis.
Supplement to: Hermoso, M et al. (2013): Black shale deposition during Toarcian super-greenhouse driven by sea level. Climate of the Past, 9(6), 2703-2712, https://doi.org/10.5194/cp-9-2703-2013